Haustorium formation and a distinct biotrophic transcriptome characterize infection of Nicotiana benthamiana by the tree pathogen Phytophthora kernoviae. (20th May 2021) - Wang, Shumei; Vetukuri, Ramesh R.; Kushwaha, Sandeep K.; Hedley, Pete E.; Morris, Jenny; Studholme, David J.; Welsh, Lydia R. J.; Boevink, Petra C.; Birch, Paul R. J.; Whisson, Stephen C.
Abstract: Phytophthora species cause some of the most serious diseases of trees and threaten forests in many parts of the world. Despite the generation of genome sequence assemblies for over 10 tree‐pathogenic Phytophthora species and improved detection methods, there are many gaps in our knowledge of how these pathogens interact with their hosts. To facilitate cell biology studies of the infection cycle we examined whether the tree pathogen Phytophthora kernoviae could infect the model plant Nicotiana benthamiana . We transformed P. kernoviae to express green fluorescent protein (GFP) and demonstrated that it forms haustoria within infected N. benthamiana cells. Haustoria were also formed in infected cells of natural hosts, Rhododendron ponticum and European beech ( Fagus sylvatica ). We analysed the transcriptome of P. kernoviae in cultured mycelia, spores, and during infection of N. benthamiana, and detected 12, 559 transcripts. Of these, 1, 052 were predicted to encode secreted proteins, some of which may function as effectors to facilitate disease development. From these, we identified 87 expressed candidate RXLR (Arg‐any amino acid‐Leu‐Arg) effectors. We transiently expressed 12 of these as GFP fusions in N. benthamiana leaves and demonstrated that nine significantly enhanced P. kernoviae disease progression and diversely localized to the cytoplasm, nucleus, nucleolus, and plasma membrane. Our results show that N. benthamiana can be used as a model host plant for studying this tree pathogen, and that the interaction likely involves suppression of host immune responses by RXLR effectors. These results establish a platform to expand the understanding of Phytophthora tree diseases. Abstract : Tree pathogen Phytophthora kernoviae forms digit‐shaped haustoria during infection of model and natural hosts, and secretes RXLR effectors that promote infection and localize to diverse cellular locations. ​